Research on the Influence of the RV-40E Reducer Modal on Its Transmission Error - Ding Guolong; Zhan Mingru; Zhao Daxing; Yu Yunqing; Dong Honggang (Jixie chuandong)
In order to reveal the influence law of RV reducer modal on transmission error, the RV-40E is used as the research object, the equivalent model method is used to construct its mass stiffness dynamic model and then the mathematical model of the RV reducer transmission error and natural frequency is established. For the intermediate stiffness, it is found that the transmission error is negatively correlated with the natural frequency. In order to verify the model, the RV-40E products of Nabtesco and domestic companies are selected to conduct a comparative test of natural frequency, stiffness and transmission error. It is found that the greater the first-order natural frequency of the RV reducer is, the greater the stiffness was and the smaller the transmission error is. The above research provides a method for the modal and performance testing of the RV reducer, and provides an important reference basis for the transformation of the RV reducer from structure design to performance design.